The meaning of resilience among adolescent cancer patients and their caregivers in Malaysia - Chaudhry, Zainab (2017)
Cancer is one of the most critical and soaring health related issues in the present times. The severity and adversity of this disease is augmented many times when it affects the young adolescents. Whilst dealing with all the illness related tautness and despondency, there are individuals and families who have managed to shield themselves against all or most of the damaging impacts. This shield emerges at the time of the diagnosis and evolves through the treatment phase till the recovery phase, characterized by the positive attributes like resilience. It reframes the life style and thought patterns from pessimism to optimism. This study ‘The Meaning of resilience amongst adolescent cancer patients in Malaysia and their caregivers’ is conducted to explore the way adolescent cancer patients and their caregivers translate the concept of resilience whilst highlighting the factors enhancing it. The study was designed in the Malaysian backdrop as there is a scarcity of local literature on adolescents, who were the main informants of the study. The study is a qualitative one conducted using the interpretive phenomenological analysis (IPA) method. The semi-structured in-depth interviews were conducted with five Muslim adolescent cancer patients and their caregivers (mothers), from Hospital Kuala Lumpur (HKL); therefore, it generated two sets of data. The patients were suffering from different types of cancer, including blood cancer, brain tumors, and bone cancer. They had been going through the active treatment phase for the last 6 to 12 months, at the time of interview. The treatment modalities included radiation, chemotherapy, bone marrow transplants, and surgeries. They all belonged to middle class families of Malaysia, five caregiving mothers, four had left their jobs due to their child’s illness. However, one mother was still working to manage the finances for the family. All the adolescents and caregiving mothers could communicate and understand English; however, some needed to explain and elaborate on the answers in the Malay language. To counter this issue, a translator, fluent in both English and Malay assisted the investigator. The results identified seven themes for data set 1 and six themes data set 2 based on the analysis of the corpuses. It was concluded from the analysis that the concept of resilience has its unique manifestation in the Malaysian culture where it is strongly influenced by the strong spiritual beliefs, emotions, family relations, and bonding, especially motherhood, along with the positive personal attitude towards life after cancer. These factors not only shaped their definition of resilience but also contributed in enhancing this positive attribute. The themes for both data sets have impact and linkage with each other, which signify the notion that resiliency like any other attribute, is deeply embedded in the families. The definition of resilience for adolescents and their caregivers is a highlight of the study which is “Resilience is a process characterized by acquiring spiritual conviction, strength of motherhood, appreciation for assets of life and recognizing the unique personal potential which help in rebounding from the adversity of illness.” The study has also proposed assumptions for the theoretical models for both adolescents with cancer and their care giving mothers; namely, the model of resiliency for adolescents with cancer (MRAC) and resiliency model of maternal stress and resilience (RMMSR). The study recommends further research in this area to cultivate the understanding of this significantly dynamic and relevant concept, based on this baseline and the preliminary study, in Malaysia. It can facilitate the health care providers and can have a wider impact on the reframing and restructuring life styles of the patients and their families after their cancer diagnosis. To reinforce, polish, and explore the resiliency capacities and positive attributes in adolescents with cancer and their caregivers, an initial outline of a counseling protocol has been proposed in the study highlighting the needs of the young patients and their caregivers, health system and culture of Malaysia.